Thermally Activated Delayed Fluorescence: Beyond the Single Molecule - Etherington, Marc K. (Frontiers in Chemistry, 2020)
Emitters that exhibit thermally activated delayed fluorescence (TADF) are of interest for commercial applications in organic light-emitting diodes (OLEDs) due to their ability to achieve internal quantum efficiency of 100%. However, beyond the intrinsic properties of these materials it is important to understand how the molecules interact with each other and when these interactions may occur. Such interactions lead to a significant red shift in the photoluminescence and electroluminescence, making them less practicable for commercial use. Through summarizing the literature, covering solid-state solvation effects and aggregate effects in organic emitters, this mini review outlines a framework for the complete study of TADF emitters formed from the current-state-of-the-art techniques.